EFEKTIVITAS KEBIJAKAN INSENTIF PAJAK DALAM MENANGGULANGI DAMPAK EKONOMI PANDEMI COVID-19 DI INDONESIA - Loso Judijanto (Prosiding Seminar Nasional Indonesia, 2025)
The COVID-19 pandemic has put significant pressure on Indonesia's economy, particularly on micro, small, and medium enterprises (MSMEs), which are the backbone of the national economy. To address this crisis, the Indonesian government has implemented various tax incentive policies as part of the National Economic Recovery (PEN) programme to maintain business continuity and promote economic recovery. This study uses a literature review method with a qualitative approach to analyse the effectiveness of tax incentive policies in mitigating the economic impact of the COVID-19 pandemic in Indonesia. The results of the study indicate that tax incentive policies, such as Government-Bearing Income Tax (PPh) 21, Final Income Tax (PPh) for MSMEs (DTP), exemption from Income Tax (PPh) 22 on imports, and reduction of Income Tax (PPh) 25 instalments, have made a positive contribution in alleviating the tax burden, maintaining cash flow, and increasing the resilience of businesses amid the economic crisis. However, the effectiveness of these policies still faces several challenges, such as the suboptimal utilisation of incentives across all sectors, insufficient outreach, and issues of misdirected targeting in the distribution of incentives. The evaluation also shows that most businesses have utilised the incentives, but tax revenue collection has decreased as a consequence of these policies, though this decline is deemed reasonable to maintain national economic stability. Overall, tax incentive policies during the pandemic can be considered quite effective in supporting national economic recovery, maintaining employment, and encouraging household consumption, although improvements are needed in socialisation, supervision, and simplification of procedures so that the benefits can be felt more widely and accurately targeted.